2015
DOI: 10.4103/0366-6999.168047
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Brain Death Criteria between China and the United States

Abstract: Background:Criteria for determining brain death (BD) vary between China and the United States. We reported the results of an investigation designed to compare procedures to determine BD in two countries.Methods:The latest criteria in the United states were published in 2010. The latest criteria in China were published in 2009. We used these two types of BD criteria to evaluate patients who were considered to be BD. The time, cost, and accuracy of the diagnosis were compared.Results:From January 1, 2012 to Octo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 13 publications
2
18
0
1
Order By: Relevance
“…These two early studies compared the EEG with clinical criteria of brain death and used paper EEG recordings which might contain substantial artifacts. A recent German study 16 (n = 67) and a Chinese study (n = 37) 17 indicated that EEG had a high sensitivity of 94%-100% which was consistent with our ndings.…”
Section: Discussionsupporting
confidence: 92%
“…These two early studies compared the EEG with clinical criteria of brain death and used paper EEG recordings which might contain substantial artifacts. A recent German study 16 (n = 67) and a Chinese study (n = 37) 17 indicated that EEG had a high sensitivity of 94%-100% which was consistent with our ndings.…”
Section: Discussionsupporting
confidence: 92%
“…For the DBD donors, the diagnosis of brain death was made by healthcare professionals from the ICU or neurology departments according to the international standardized methods and the brain death criteria published by the Ministry of Health of People's republic of China. 7,8 The second brain death determination was made after observation for 12-24 hours. After determination of second brain death, the donor was transferred to operation room for withdrawing lifesupporting treatment and organ procurement.…”
Section: Methodsmentioning
confidence: 99%
“…There is no uniform neurological standard in death determination because of the variability in practices and perceptions of the global medical community about brain death (Wahlster et al 2015 ). The neurological determination of death varies among countries with regard to the use of whole brain criteria or brainstem criteria, and the mandatory performance of confirmatory tests (Ding et al 2015 ; Citerio and Murphy 2015 ; Chua et al 2015 ; Varelas 2016 ; Cameron et al 2016 ). Confirmatory tests include neuroimaging of cerebral blood flow and electrophysiological studies of the cerebral hemispheres and the brainstem.…”
Section: Introductionmentioning
confidence: 99%